Seismic failure analysis of concrete bridges exposed to scour. (September 2020) - Zaky, Akram; Özcan, Okan; Avşar, Özgür
Highlights: The seismic performance of the case study bridge was evaluated under scouring. Scour depth increase led to higher periods, lateral deflections and accelerations. Pier column internal forces reduced while increasing pile internal force demands. The piles exhibited significant plastic rotations with the increase in scour depth. After scouring, plastic hinging migrated and spread from pier columns to piles. Scour induced hinge development on piles violates capacity design principles. Bridge behavior under multi-hazard events has to be concerned in seismic design. Abstract: Scouring has been known as one of the most frequent cause of failure observed in bridge infrastructures. Not to mention, the evaluation of scour mechanism sheds light on pile foundation design and helps to prevent scour induced structural deficiencies. Thus, the scouring mechanism around bridge pile foundations should be extensively evaluated in order to predict the bridge safety under critical multi-hazard environment. In this study, the local scour mechanism around bridge piles was appraised considering discrete element methods (p-y curves) in order to reflect the nonlinear nature of soil structure interaction (SSI). Following that, bridge seismic behavior and relevant failure mechanism was evaluated with regard to nonlinear time history analyses (THA). In the conducted research, river crossing 7 – span Boğaçay Bridge located in Antalya, Turkey was selected as the case study. After SAP2000 finite element modeling (FEM), the bridge was exposed to twelve incremental scour depths up to six meters at all piers and was subject to subsequent seismic effects as concordant to the site that mimics a probable earthquake occurs after scouring regarding the Turkish Earthquake Code (TEC-2018). The modal responses indicated a simultaneous increase in natural periods with augmenting scour depth. In the analyses, the influence of scouring on pier displacement demands, pier accelerations and the internal forces at piers and piles were investigated. The analysis results indicated a significant increase in pier displacement demands with increasing scour depth especially in the transverse direction of the bridge. Further, due to the migration and spreading of plastic hinging from piers to piles due to scouring, the internal forces that were resisted by the strong axis of the pier columns decreased significantly. This fact led to the increase in pile bending moments and rotations in both orthogonal directions of the bridge. Thus, it was concluded that the probable multi-hazard effects of scouring and earthquake in river crossing bridges should be considered in bridge substructure design.